The impact of vertical integration on inventory turnover and operating performance - Andreou, Panayiotis; Louca, Christodoulos; Panayides, Photis (My University, 2016)
This paper investigates how vertical integration may influence inventory turnover and firm operating performance. A causal model is developed to investigate the effects of vertical integration on three types of inventory, namely raw materials inventory (RMI), work in progress inventory (WIPI) and finished goods inventory (FGI). The model tests the interactions between inventory types and the consequences of inventory turnover performance on various aspects of firm performance including costs and profitability. In particular, path analysis supports systematic differences with respect to how vertical integration affects RMI, WIPI and FGI. Vertical integration has a positive effect on RMI and FGI turnover but no significant effect on WIPI turnover. FGI contributes to a reduction in supporting processes costs which causes an improvement in return on sales (ROSs). Vertical integration impacts ROS directly.
Keywords: Inventory; Supply chain management; Vertical integration